The Implementation of Direct Learning Model With Guided Discovery Approach To Improving Learning Effectiveness Through on Circle Theory In SMP Islam Terpadu Ar-Rahmah Makassar - Rahmawati Rahmawati; Masli Nurcahya Zoraida (Journal of Research and Multidisciplinary, 2022)
This type of research is classroom action research which was carried out for two cycles, which aims to improve mathematics learning outcomes through a guided discovery approach with a direct learning model. The subjects of this study were 26 students of class VIII SMP Islam Terpadu Ar-Rahmah Makassar with a composition of 21 male students and 5 female students. The results of this study indicate that: (1) the average score of students in cycle I is 61.38 from the ideal score of 100 with a standard deviation of 11.85 and is in the medium category. There are 10 students who finished studying individually. (2) The average score of students in the second cycle is 75.60 from the ideal score of 100 with a standard deviation of 15.37 and is in the high category. There are 21 students who have finished studying individually. (3) There was an increase in the activeness and attention of students in learning mathematics. From the results of the analysis, it can be concluded that applying the guided discovery approach can improve the mathematics learning outcomes of class VIII SMP Islam Terpadu Ar-Rahmah Makassar.